Atrial arrhythmias after lung transplant: Underlying mechanisms, risk factors, and prognosis - Orrego, Carlos M.; Cordero-Reyes, Andrea M.; Estep, Jerry D.; Seethamraju, Harish; Scheinin, Scott; Loebe, Matthias; Torre-Amione, Guillermo (The Journal of heart and lung transplantation, 2014)
Atrial arrhythmias (AAs) early after lung transplant are frequent and have a significant impact on morbidity and mortality. However, the pathogenesis of AAs after lung transplant remains incompletely understood. In this study we aimed to determine the prevalence of atrial fibrillation (AF) and other AAs, as well as risk factors, clinical outcomes and possible underlying mechanisms associated with AAs after lung transplant. A retrospective analysis was performed on 382 patients who underwent lung transplantation from 2000 to 2010. A 12-lead electrocardiogram (ECG) was obtained and AAs classified as AF and other AAs (atrial flutter [AFL] and supraventricular tachycardia [SVT]). Multivariate logistic regression analysis was performed to determine predictors, and Kaplan–Meier survival curves were constructed. The incidence of AAs was 25%; 17.8% developed AF and 7.6% other AAs (AFL/SVT). The major indication for transplant was idiopathic pulmonary fibrosis (IPF, 35%). Significant predictors of AF were as follows: age; IPF; left atrial enlargement; diastolic dysfunction; and history of coronary artery disease (CAD). Risk factors for other AAs (AFL/SVT) were: age; right ventricle dysfunction; right ventricular enlargement; and elevated right atrial pressure (RAP). One-year mortality was higher in the arrhythmia group (21.5% arrhythmia vs 15.7% no-arrhythmia group; p < 0.05). In addition, patients treated with anti-arrhythmic medications had higher mortality (p < 0.05). AAs are common after lung transplantation. Risk factors for developing either AF or other AAs (AFL/SVT) are different. The development of early AAs post-transplant is associated with prolonged post-operative stay and increased mortality. A rate-control strategy should be used as first-line therapy and anti-arrhythmic agents reserved for those patients who do not respond to the initial treatment.